Control mechanisms of mammalian pepsinogen secretion - Modlin, Irvin M (Division of Surgical Gastroenterology, 2018)
The objective of this thesis was to delineate aspects of the control mechanisms of mammalian pepsinogen secretion. In order to accomplish this goal, a comprehensive study was undertaken which would establish an historical perspective of the subject, validate appropriate methodology and then seek to answer specific questions regarding the physiology and pathophysiology of pepsinogen secretion. More specifically, the objectives of this thesis were: 1. To review the historical background of the subject of pepsinogen in the context of the physiology of digestion with specific emphasis on the work and lives of the two major initial proponents of pepsinogen research (Schwann and Langley). 2. To provide a contemporary overview and evaluation of the current status of pepsinogen pathophysiology. 3. To modify and adapt experimental models necessary for the study of pepsinogen and acid secretion in mammalian gastric mucosa and cells. 4. To establish and validate a pepsinogen assay sensitive and reproducible enough for use in mammalian mucosa! and cellular secretory systems. 5. To delineate the fundamental (second messenger) control mechanisms (cyclic AMP and calcium calmodulin) of pepsinogen secretion in the isolated gastric gland model. 6. To define whether the process of pepsinogen secretion is independent of acid secretion in intact mucosa! preparations. 7. To identify different classes of pharmacological agents which would inhibit pepsinogen secretion and/or release. 8. To identify whether conditions present in critically ill patients liable to mucosal "stress ulceration" might influence the release of pepsinogen.